Pengaruh Perbandingan Bahan Pelarut dan Lama Ekstraksi terhadap Karakteristik Ekstrak Pewarna Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) - Dwipayana, I Made; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
Dyes from fragrant pandan leaves contain chlorophyll obtained through the extraction process. The purpose of this study were to determine the effect of the ratio of ingredients to solvents and the length of extraction on the characteristics of natural coloring extracts of fragrant pandan leaves and determine the best treatment from the comparison of ingredients with solvents and extraction time to produce natural coloring extracts of fragrant pandan leaves. This study used a 2 factor factorial randomized block design. The first factor is the comparison of materials with solvents consisting of 3 levels, namely 1:13, 1:15, and 1:17. The results showed that the comparative treatment of the material with the solvent and the extraction time greatly influenced the extract yield, chlorophyll a levels, chlorophyll b levels, total chlorophyll levels, brightness level L *, redness level a *, yellowish level b *, interactions greatly influenced the levels chlorophyll a, chlorophyll b level, total chlorophyll content, redness level (a *), yellowish level (b *) but have no effect on extract yield and brightness level (L *). Comparison of material treatment with solvent 1:15 and extraction time for 36 hours, is the best treatment to produce pandanus fragrant leaf extract coloring with extract yield characteristics of 10.32%, chlorophyll a levels of 3402.04 ppm, chlorophyll b levels of 612.23 ppm, total chlorophyll content of 4013.42 ppm, brightness level (L *) 35.27, redness level (a *) 17.15, yellowish level (b *) 30.43. Keywords: Pandanus amaryllifolius Roxb., chlorophyll, nature color, extraction.